Letters to Gwen John - Paul, Celia 1959- (Vintage, 2024)
"We are both painters. We can connect to each other through images, in our own unvoiced language. But I will try and reach you with words. Through talking to you I may come alive and begin to speak. Celia Paul has felt a lifelong connection to the artist Gwen John. There are extraordinary parallels in their lives and work. Both have always made art on their own terms. Both were involved with older male artists. Both worked hard to keep themselves and the sacred flame of their creativity from being extinguished by others. Letters to Gwen John is Paul's imagined correspondence with Gwen John, whose life and work have loomed so large in hers. These intimate, passionate, haunting letters allow Paul to reach across eras, to weigh up the sacrifices she has made, and to explore the rich possibilities of a life apart. With illuminating insights into the life and work of Gwen John, Letters to Gwen John is a unique form of memoir and conversation, and an unforgettable insight into a life devoted to making art"--Publisher's description
"Letters to Gwen John is Paul's imagined correspondence with this groundbreaking painter." First published in hardback by Jonathan Cape in 2022
Keywords: John, Gwen -- 1876-1939; Paul, Celia -- 1959-; Rezeption; Malerei; Paul, Celia / 1959- / Correspondence; John, Gwen / 1876-1939 / Influence; John, Gwen; Paul, Celia; Women painters / Great Britain / Biography; Painters / Great Britain / Biography; Influence (Literary, artistic, etc.); Painters; Women painters; Personal correspondence; Biographies; Great Britain